2019
DOI: 10.1002/isd2.12117
|View full text |Cite
|
Sign up to set email alerts
|

A model for mobile money services adoption by traders in Uganda

Abstract: Mobile money services provide benefits for trade such as payment of bills, reduced cost and time for transactions, increased savings options, sales, and convenience. Despite the benefits, adoption and use of mobile money services by traders in Uganda remain low. This paper reports on the results of a study that explore the challenges traders face in using and adopting mobile money services in Uganda. Self‐administered questionnaire was used to collect data from 394 respondents in a survey. A model to support m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…In response, this research extends previous studies by adopting a combinatorial approach to evaluate pathways through which mobile money can be used to improve financial inclusion. Malinga and Maiga (2020) Explore challenges traders face in using and adopting mobile money services -Quantitative method -Regression analysis UTAUT Lashitew et al (2019) Examines factors that affect the development and diffusion of mobile money services -Mixed method -Tobit regression analysis and case study Technology innovation and Power-interest framework Lepoutre and Oguntoye (2018) Seeks to understand mechanisms that explain these differences in mobile money adoption rate across different countries through a comparative case study analysis of Kenya and Nigeria -Comparative case study -Cross-case analysis Sociotechnical transformation and innovation ecosystems Rahman et al (2017) Examines the influence of optimism, innovativeness, discomfort and insecurity on bKash 1 entrepreneurs' perceived ease of use (PEOU) and perceived usefulness (PU) of bKash technology as well as effect of 'bKash' entrepreneurs' PEOU and PU on their well-being.…”
Section: Financial Inclusion Through Mobile Moneymentioning
confidence: 99%
See 2 more Smart Citations
“…In response, this research extends previous studies by adopting a combinatorial approach to evaluate pathways through which mobile money can be used to improve financial inclusion. Malinga and Maiga (2020) Explore challenges traders face in using and adopting mobile money services -Quantitative method -Regression analysis UTAUT Lashitew et al (2019) Examines factors that affect the development and diffusion of mobile money services -Mixed method -Tobit regression analysis and case study Technology innovation and Power-interest framework Lepoutre and Oguntoye (2018) Seeks to understand mechanisms that explain these differences in mobile money adoption rate across different countries through a comparative case study analysis of Kenya and Nigeria -Comparative case study -Cross-case analysis Sociotechnical transformation and innovation ecosystems Rahman et al (2017) Examines the influence of optimism, innovativeness, discomfort and insecurity on bKash 1 entrepreneurs' perceived ease of use (PEOU) and perceived usefulness (PU) of bKash technology as well as effect of 'bKash' entrepreneurs' PEOU and PU on their well-being.…”
Section: Financial Inclusion Through Mobile Moneymentioning
confidence: 99%
“…Application of the UTAUT Patil et al (2020) Extended UTAUT with personal innovativeness, anxiety, trust, and grievance redressal to examine consumer use behaviour towards mobile payment Malinga and Maiga (2020) Extended UTAUT with security and sensitization to investigate mobile money adoption among traders Based on the UTAUT, this study presents a model (see Figure 1) to address the research question. Following a combinatorial approach, we represent the five conditions in a Venn diagram to signify various pathways through which mobile money can be used to improve financial inclusion.…”
Section: Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large body of literature on the factors that impede the growth of mobile money services. The following factors were identified from various empirical contexts: income [6,10,11], bank account ownership [9,11,13]; age [14,15], education [10,16], sex [10,15], employment status [10,17], ease of use [6,13], perceived risk and trust [18,19] and awareness of services and benefits [17,20]. The review on factors delaying growth of mobile money from other literatures indicated that this subject is broader than what meets the eye.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A sample of key strategies were analysed. These included float management [21,22] customer loyalty [21,23]; a strong social and agent network [21,22], simplification of the registration process [6,20,24]; effective regulation [20], and mobile money fees [20,23] Theories that had been advanced to explain the factors that impede the growth of business, including mobile money agents were reviewed. The theoretical framework highlighted three of these theories.…”
Section: Literature Reviewmentioning
confidence: 99%